Discrete an SIS model with immigrants and treatment. Issue 5 (4th July 2021) - Shalan, Rehab Noori; Shireen, R.; Lafta, Alaa Hussien
Abstract: In this paper, a discrete SIS epidemic model with immigrant and treatment effects is proposed. Stability analysis of the endemic equilibria and disease-free is presented. Numerical simulations are conformed the theoretical results, and it is illustrated how the immigrants, as well as treatment effects, change current model behaviour.